The Influence of Sensitization Temperature to Tensile Strength, Microstructure, and Hardness of AISI 309 Stainless Steel - Anggawisnu, Bayuardi
AISI 309 is one of the stainless steels group which also has a good resistance to high temperature. Besides, AISI 309 is known as stainless steel with good mechanical properties, such as the toughness and ductility. AISI 309 is used for high temperatur application. For example, for a structure in a furnace. But, its mechanical properties will change as a result of heating. This experiment is conducted to determine the influence of heat or sensitization temperature to the formation of carbides that change mechanical properties. Sensitization is done by heating specimen in at temperatures of 600, 700, 800, and 900oC for 100 hours. Sensitization is a process which chromium and carbon forms a coumpound, chromium carbides along grain boundaries. That carbides will modify the hardness and tensile strength of AISI 309. To observe the change caused by carbides precipitation, several test have to be done, such as tension test, microvickers hardness test, metallography, optical microscope and SEM characterization, and calculation of carbide fraction. The result shows that the increase sensitization temperature, will decrease the hardness and yield strength, but increase the tensile strength.